Ecophysiological distinctions of haloarchaea from a hypersaline Antarctic lake determined using metaproteomics. - Tschitschko, B; Williams, TJ; Allen, MA; Zhong, L; Raftery, MJ; Cavicchioli, R (Applied and Environmental Microbiology, 2016)
Deep Lake in the Vestfold Hills is hypersaline and the coldest system in Antarctica known to support microbial growth (temperature as low as -20°C). It represents a strong experimental model because the lake supports a low complexity haloarchaea community, with the three most abundant species totalling ∼72%. Moreover, the dominant haloarchaea are cultivatable and their genomes are sequenced. Here we use metaproteomics linked to metagenome data and the genome sequences of the isolates to characterize the main pathways, trophic strategies, and interactions associated with resource utilization. The dominance of the most abundant member, Halohasta litchfieldiae, appears to be predicated on competitive utilization of substrates (e.g. starch, glycerol, dihydroxyacetone) produced by Dunaliella, the lake's primary producer, while also possessing diverse mechanisms for acquiring nitrogen and phosphorus. The second most abundant member, DL31, is proficient in degrading complex proteinaceous matter. Hht. litchfieldiae and DL31 are inferred to release labile substrates that are utilized by Halorubrum lacusprofundi, the third most abundant haloarchaeon in Deep Lake. The study also linked genome variation to specific protein variants or distinct genetic capacities, thereby identifying strain level variation indicative of specialization. Overall the metaproteomics revealed that rather than functional differences occurring at different lake depths or through size partitioning, the main lake genera possess major trophic distinctions, and phylotypes (e.g. strains of Hht. litchfieldiae) exhibit a more subtle level of specialization. The study highlights the extent to which the lake supports a relatively uniform distribution of taxa that collectively possess the genetic capacity to effectively exploit available nutrients throughout the lake. IMPORTANCE: Life on Earth has evolved to colonize a broad range of temperatures, but most of the biosphere (∼85%) exists at low temperatures (≤5°C). By performing unique roles in biogeochemical ...